3D Computed Tomography Quantifies the Dependence of Bulk Porosity, Surface Roughness, and Re‐Entrant Features on Build Angle in Additively Manufactured IN625 Lattice Struts. Issue 6 (24th September 2021) - Fritsch, Tobias; Farahbod-Sternahl, Lena; Serrano-Muñoz, Itziar; Léonard, Fabien; Haberland, Christoph; Bruno, Giovanni
Abstract : Layer‐by‐layer additive manufacturing (AM) by means of laser‐powder bed fusion (L‐PBF) offers many prospects regarding the design of lattice structures used, for example, in gas turbines. However, defects such as bulk porosity, surface roughness, and re‐entrant features are exacerbated in nonvertical structures, such as tilted struts. The characterization and quantification of these kinds of defects are essential for the correct estimation of fracture and fatigue properties. Herein, cylindrical struts fabricated by L‐PBF are investigated by means of X‐ray computed tomography (XCT), with the aim of casting light on the dependence of the three kinds of defects (bulk porosity, surface roughness, and re‐entrant features) on the build angle. Innovative analysis methods are proposed to correlate shape and position of pores, to determine the angular‐resolved surface roughness, and to quantify the amount of re‐entrant surface features, q . A meshing of the XCT surface enables the correlation of q with the classical surface roughness P a . This analysis leads to the conclusion that there is a linear correlation between q and P a . However, it is conjectured that there must be a threshold of surface roughness, below which no re‐entrant features can be build. Abstract : The porosity and the surface quality of seven additively manufactured struts are investigated by means of laboratory computed tomography in dependence of the build angle. A workflow for the quantitative analysis of re‐entrant surface features is presented based on the meshed CT‐surface. The amount of re‐entrant features is correlated to conventional mean roughness parameter.